PENGARUH BERMAIN BOLA KATA DALAM MENINGKATKAN KEMAMPUAN BERBICARA ANAK USIA DINI DI TK AISYIYAH BUSTANUL ATHFAL KRAGILAN - Masamah, Mamah; Sari, Novita; Risna, Inten (LPPM Universitas Bina Bangsa, 2024)
This study is motivated by the results of observations of researchers in the field conducted at Aisyiyah Bustanul Athfal Kragilan Kindergarten, Serang Regency. Problems were found in speaking ability, namely children have not been able to describe a word into a sentence and children have not been able to speak fluently. This is due to the use of inappropriate learning methods and a less pleasant learning atmosphere for children. The purpose of this study was to improve speaking skills in early childhood at Aisyiyah Bustanul Athfal Kragilan Kindergarten and to examine how word ball games can improve speaking skills in early childhood at Aisyiyah Bustanul Athfal Kragilan Kindergarten. The research subjects were group B children totaling 10 children, data were networked with observation documentation and analyzed by means of data reduction, data presentation and conclusion drawing. The results showed that the application of word ball games in group B children can run well according to plan, this is evidenced by the results of observations of teacher activities that are carried out in accordance with the steps in the application of word ball games and the results of observations show that children's abilities have also increased. From the data analysis, it can be concluded that the application of word ball games can improve the speaking ability of group B children at Aisyiyah Bustanul Athfal Kragilan Kindergarten. Word ball games can be applied in schools to improve speaking skills in early childhood because word ball games are in accordance with the language skills of children aged 5 to 6 years